Molecular alterations in signal pathways of melanoma and new personalized treatment strategies: Targeting of Notch - Julija Mozūraitienė; Kristina Bielskienė; Vydmantas Atkočius; Danutė Labeikytė (Medicina, 2015)
Despite modern achievements in therapy of malignant melanomas new treatment strategies are welcomed in clinics for survival of patients. Now it is supposed that personalized molecular therapies for each patient are needed concerning a specificity of molecular alterations in patient's tumors. In human melanoma, Notch signaling interacts with other pathways, including MAPK, PI3K-AKT, NF-kB, and p53. This article discusses mutated genes and leading aberrant signal pathways in human melanoma which are of interest concerning to their perspective for personalized treatment strategies in melanoma. We speculate that E3 ubiquitin ligases MDM2 and MDM4 can be attractive therapeutic target for p53 and Notch signaling pathways in malignant melanoma by using small molecule inhibitors. It is possible that restoration of p53-MDM2-NUMB complexes in melanoma can restore wild type p53 function and positively modulate Notch pathway. In this review we summarize recent data about novel US Food and Drug Administration approved target drugs for metastatic melanoma treatment, and suppose model for treatment strategy by targeting Notch.